Inequalities for jacobians: interpolation techniques (1993)
Recently new and surprising integrability properties were discovered for the Jacobians of orientation preserving maps. These results have interesting applications to variational problems in elasticity theory, compensated compactness and other areas. We review some of the main results and present new estimates that resolve some open problems in the area. Our methods are based on techniques from Interpolation theory.